2013
DOI: 10.1104/pp.113.219147
|View full text |Cite
|
Sign up to set email alerts
|

Coordination between Apoplastic and Symplastic Detoxification Confers Plant Aluminum Resistance

Abstract: Whether aluminum toxicity is an apoplastic or symplastic phenomenon is still a matter of debate. Here, we found that three auxin overproducing mutants, yucca, the recessive mutant superroot2, and superroot1 had increased aluminum sensitivity, while a transfer DNA insertion mutant, xyloglucan endotransglucosylase/hydrolases15 (xth15), showed enhanced aluminum resistance, accompanied by low endogenous indole-3-acetic acid levels, implying that auxin may be involved in plant responses to aluminum stress. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 58 publications
4
86
0
Order By: Relevance
“…The auxin accumulation in the TZ mimics the root growth inhibition induced by an external supply of auxin, much of which is taken up by the TZ . A recent report, which showed that auxin enhances Al toxicity via an alteration in ALUMINUM-SENSITIVE1-mediated Al distribution (Zhu et al, 2013), provides further support for our findings. Unfortunately, the study of Zhu et al (2013) made no attempt to define the spatial correlations between Al and auxin effects in the root apex during the Al-induced inhibition of root growth.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The auxin accumulation in the TZ mimics the root growth inhibition induced by an external supply of auxin, much of which is taken up by the TZ . A recent report, which showed that auxin enhances Al toxicity via an alteration in ALUMINUM-SENSITIVE1-mediated Al distribution (Zhu et al, 2013), provides further support for our findings. Unfortunately, the study of Zhu et al (2013) made no attempt to define the spatial correlations between Al and auxin effects in the root apex during the Al-induced inhibition of root growth.…”
Section: Discussionsupporting
confidence: 90%
“…The importance of the properties of the cell wall in the context of Alinduced inhibition of root elongation and in Al tolerance has been emphasized . The binding of Al to the cell wall, and particularly to the pectic and hemicellulosic matrix in the most Al-sensitive zone of the root apex, has a major effect on cell wall properties and root growth in Arabidopsis (Yang et al, 2011a;Yang et al, 2011b;Zhu et al, 2012Zhu et al, , 2013. The binding of Al to pectins is known to be highly dependent on their degree of methylation: binding occurs preferentially to unmethylated pectin, catalyzed by the activity of pectin methylesterase (PME) Yang et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that hemicellulose contributes greatly to the metal binding in cell walls of rice and Arabidopsis (Yang et al, 2008(Yang et al, , 2011Zhu et al, 2012Zhu et al, , 2013. Here, we found that -Fe+Put treatment significantly decreased hemicellulose content compared with -Fe treatment alone (Fig.…”
Section: Put Induces Fe Remobilization From the Root Cell Wall Hemicesupporting
confidence: 56%
“…The roots were then frozen at 280°C overnight. The root-cell sap solution was obtained by thawing the samples at room temperature, and then the liquid was collected after centrifuging at 20,600g for 10 min according to Zhu et al (2013). The soluble Fe, total Fe, and symplastic Fe content were determined by ICP-AES (IRIS/AP optical emission spectrometer).…”
Section: Measurements Of Fe Content In Plantsmentioning
confidence: 99%
See 1 more Smart Citation